1977
DOI: 10.1128/aac.12.6.655
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B and Rifampin: New Regimen for Multiresistant Serratia marcescens Infections

Abstract: Polymyxin B and rifampin were given to 12 patients with multi-drug-resistant nosocomial Serratia marcescens infections. Eight cures were achieved; drug hepatotoxicity occurred once; one fatal suprainfection was encountered; and two patients died during therapy of causes related to severe underlying illnesses. Polymyxin B and rifampin were uniformly synergistic in vitro against the infecting strains and against 40 additional clinical isolates ofS. marcescens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…On the other hand, TMP-SMZ combined with carbenicillin was synergistic against 12 of 14 isolates by the checkerboard method (Table 2). An isobologram generated by the checkerboard method is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, TMP-SMZ combined with carbenicillin was synergistic against 12 of 14 isolates by the checkerboard method (Table 2). An isobologram generated by the checkerboard method is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Infections caused by this organism have posed special problems because it is generally resistant to many of the commonly used antimicrobial agents, including those active against Pseudomonas aeruginosa (9,11,12,18,21). Because of recent reports of endocarditis caused by P. maltophilia (6,21), we have studied the in vitro antimicrobial susceptibilities of 14 clinical isolates to 18 antimicrobials singly and in combination. Results of susceptibility testing with sisomicin, netilmicin, rifampin, cefamandole, cefoxitin, cefotaxime, and LY127935 have not been previously reported.…”
mentioning
confidence: 99%
“…Against P. aeruginosa, combinations with rifampin produced synergistic killing in 90% to 100% of isolates in all but one study; the difference in the latter study may have been the use of colistimethate rather than colistin sulfate or polymyxin B. Synergy was also demonstrated in a few studies using azithromycin or imipenem, but antagonism was also rarely observed. The combination of polymyxins with rifampin also showed bactericidal synergy against isolates of K. pneumoniae, S. maltophilia, and S. marcescens (20,58,134,173).…”
Section: Bactericidal Activity and Synergy Studiesmentioning
confidence: 92%
“…The findings of time-kill studies involving polymyxins against A. baumannii (26, 60, 160, 170, 187), P. aeruginosa (19,59,67,93,139,171), Stenotrophomonas maltophilia (58), K. pneumoniae (20), and S. marcescens (134,173) are summarized in Table 5. Against A. baumannii, the combination of polymyxin B or colistin with rifampin produced synergistic activity (generally defined as a Ն100-fold increase in killing) against most isolates.…”
Section: Bactericidal Activity and Synergy Studiesmentioning
confidence: 99%
“…The susceptibility of the 36 strains of P. aeruginosa was determined for ticarcillin and tobramycin alone and in combination by a previously described microtiter broth dilution checkerboard method (8,17). Each test was performed in duplicate, and all strains were tested in parallel in each of 12 media by this method.…”
mentioning
confidence: 99%